Désindustrialisation, désenchantement et vote d’extrême droite - Maurice Carrez (Cahiers d’histoire)
This book aims to show, in a nuanced and precise way, the effects of deindustrialization on a territory of eastern France. This can change the electoral behaviour of a population whose habits have been upset by the closure of businesses and the dislocation of the community they helped to forge. Another development contributes to these changes: the aging of the population and the departure of young people, which is accelerating after the 2000s. The old world also began to disintegrate under the influence of factors such as the entry into the consumer society and the weakening of religious practices.